Information-based trade in the Shanghai stockmarket - Laurence Copeland; Woon K. Wong; Y Zeng (Cardiff University, Cardiff Business School, 2008)
We show that the probability of information-based trade (PIN) played a significant role in explaining monthly returns on Shanghai A shares over the period 2001 to 2006. In particular, PIN, as approximated by order imbalance as a proportion of total transactions, appears to explain returns even after controlling for risk in the much-cited Fama and French [Fama, E. F. & French, K. R. (1992). The Cross-Section of Expected Stock Returns. Journal of Finance, XLVII, 427-465.] three-factor model. However, we also find that some of the PIN effect appears to be indistinguishable from a turnover effect.
Keywords: 330; Information-based trade Asset pricing Shanghai Stock Exchange; Aktienmarkt; Asymmetrische Information; Kapitalertrag; China